Business consulting, knowledge absorptive capacity, and innovativeness: A triangular model for micro and small enterprises in Poland - Wojciech Grabowski; Edward Stawasz (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: This paper proposes a triangular relationship between business consulting, knowledge absorptive capacity, and innovativeness. The role of knowledge absorptive capacity in stimulating the impact of business consulting on innovativeness is studied. METHODOLOGY: An empirical study is conducted using the CATI method, and it is based on data concerning 382 Polish micro and small enterprises. Qualitative variables reflecting using business consulting, knowledge absorptive capacity and innovativeness are defined. The multivariate discrete choice model taking into account relationships among these constructs, is proposed and its parameters are estimated. FINDINGS: The results of the empirical research indicate that business consulting in Poland and similar countries may help firms implement innovative solutions. Knowledge absorptive capacity stimulates innovativeness and has a positive impact on the relationship between using business consulting and improvement in innovativeness. Though the frequency of using business consulting is an important factor in improving innovativeness, cooperation between a consultant and a manager matters more. IMPLICATIONS: Results of the empirical research indicate that cooperation between a consultant and a manager may help reduce differences of opinion and internal conflicts. A higher propensity to cooperate may significantly improve the functioning of an enterprise. Business consulting has an indirect and direct effect on innovativeness. It has a positive impact on knowledge absorptive capacity, while better knowledge stimulates innovativeness. ORIGINALITY AND VALUE: An original triangular model of the relationship between business consulting, knowledge absorptive capacity, and innovativeness is proposed. Advanced econometric methods are used in order to find complex relationships between using business consulting, knowledge absorptive capacity, and improvement in innovativeness. Moreover, results of the estimation of the parameters of the econometric model provide interesting recommendations for policies supporting the development of business consulting in the Polish economy.